Pengaruh Kesadaran, Sanksi Pajak, Kualitas Pelayanan Pajak, dan Penerapan Sistem Samsat Drive Thru Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Nur Aeni, Tati; Budyastuti, Triyani (Gorontalo Accounting Journal, 2024)
This study aims to examine the effect of taxpayer awareness, tax sanctions, tax service quality, and the application of samsat drive thru system on motor vehicle taxpayer compliance. The population in this study is all motor vehicle taxpayers who have been registered at the West Jakarta Samsat Joint Office. This study used nonprobability sampling techniques, accidental sampling was 105 respondents. For data collection techniques using questionnaires and Data analysis techniques using SMARTPLS 3. The results of this study show that taxpayer awareness, tax sanctions and the implementation of the SAMSAT drive thru system have a positive and significant effect on motor vehicle taxpayer compliance. Meanwhile, the quality of tax services does not have a positive and significant effect on the compliance of motor vehicle taxpayers at the SAMSAT Joint Office in West Jakarta.